Legal Protection for Buyers of Objects Mortgage Rights in Registering Transfers of Land Rights That Become the Object of Auction Collateral - Safriani, Vini Nurul; Saraswati, Nabila Trina Saumah; Maskanah, Ummi (Golden Ratio of Data in Summary, 2025)
Parate Executive or direct execution, namely the execution of mortgage rights, which is carried out by selling the object of the mortgage right by the first mortgage holder on his power through a public auction and taking the debt payment from the sale proceeds. Protection of mortgage auction has been carried out in a preventive manner by the State Wealth and Auction Service Office (KPKNL) because before the auction, KPKNL notifies the auction participants regarding the documents, conditions, and conditions of the object to be auctioned in truth and as it is as well as the consequences and risks that may arise from the auction object. Regarding repressive protection, namely efforts to obtain legal protection through judicial bodies and obstacles to implementation, there is no agreement on the price of the object being auctioned.